Growth and antioxidant content of pegaga (Centella asiatica (L.) Urban), inoculated with plant growth- promoting rhizobacteria - Surimin, Adilah (2016)
Pegaga (Centella asiatica) has been recognized as a medicinal plant which contains valuable antioxidant compounds; phenolic and flavonoid, the pharmacologically active ingredients which are beneficial for human body system. Unfortunately, these bioactive compounds are present at lower concentrations in plant extracts. Plant Growth-Promoting Rhizobacteria (PGPR) which work as elicitors, can be an effective method to stimulate growth and expression of antioxidants in Pegaga. The experiments were conducted under soilless conditions to clearly observe the effect of PGPR on plant growth and bioactive compound. Beneficial PGPR were isolated from Pegaga roots and was evaluated based on plant biochemical assays, formation of phytohormone Indole-3-acetic acid (IAA), N2-fixation, and P and K-solubilizations. From the 16 isolates, two bacterial strains C3E2 (UPMB30) and C1R1 (UPMB31) showed maximum plant growth promoting abilities and were further identified based on colony morphology, Gram-staining and characterized through 16S rRNA gene sequencing. UPMB30, an endobacterial isolate was 99% identified as Bacillus subtilis and UPMB31, a rhizobacterial isolate, as an Stenotrophomonas maltophilia. To achieve the second objective, a few factors and critical issues were verified to ensure these PGPR isolates could function under soilless condition. The selected PGPR strains were then exposed to various soilless culture conditions: pH (4.0, 5.0 and 6.0), fertilizer concentrations (50%, 100%, 200%) and bacterial population densities (104cfu/mL, 109cfu/mL and uninoculated) to determine the optimum combination of fertilizer and inoculum sized. The results showed high survivability and growth of bacterial strains in the following descending order; pH 4.0>5.0>6.0 and fertilizer concentration 50%>100%>200%. Application of 104cfu/mL bacteria with 50% fertilizer rate increased 12% of yield and saves 50% of chemical fertilizer input. The high inoculum size, 109cfu/mL however, reduced plant growth length and led to over colonization and possibly became harmful to the plant. Antioxidant and their interactions with PGPR were evaluated in the final experiment. Free radical scavenging assay (DPPH): 1,1- diphenyl-2- picrylhydrazyl; Total Phenolic Content (TPC): Folin-Ciocalteu assay; and Total Flavonoid Content (TFC): Aluminium chloride method assay were analyzed. Results demonstrated high concentrations of DPPH, TPC and TFC in extracts taken from all the three parts of Pegaga (roots, leaves, stems), irrespective of PGPR strains. The increase in antioxidant synthesis presumably represents a defensive response to colonization by PGPR. Results showed all strains highly colonized in the roots (106 to 107 CFU/mL). Highly reduced levels of proline content were observed in the inoculation treatment for all strains compared to the uninoculated control; UPMB10 (52.06 μg/fw), UPMB31 (44.33 μg/fw), UPMB30 (31.54 μg/fw) and uninoculated control (98.69 μg/fw). In conclusion, this study clearly indicated that two potential isolated strains (UPMB30 and UPMB31) could be applied as elicitors to significantly increase vegetative growth of Pegaga and antioxidant contents in the plants.